Optimizing the Role of the Interfaith Youth Generation in Bali to Promote Tolerance and Peace in the Digital Era - Sari Dewi Noviyanti; David Ilham Yusuf (LPPM Universitas HKBP Nommensen, 2025)
This community service project aims to optimize the role of the interfaith youth generation in Bali in fostering tolerance and peace, particularly in the context of the digital era. As digital platforms become increasingly influential in shaping public discourse, it is crucial to harness their power for positive social change. The project will engage youth from diverse religious backgrounds, providing them with the tools and knowledge necessary to navigate online spaces responsibly. Through workshops, interfaith dialogues, and digital literacy training, participants will be empowered to promote messages of mutual respect, tolerance, and peace. The project will also focus on combating online hate speech and misinformation, while encouraging youth to use social media as a platform for unity and understanding. By nurturing a generation of digitally-savvy, tolerant youth, this initiative seeks to contribute to a more harmonious and peaceful society in Bali.